Sacred space: an approach to the theology of the Epistle to the Hebrews - Isaacs, Marie E. (Journal for the study of the New Testament / Supplement series, 1992)
The author of Hebrews is not preoccupied with the concepts of the Hellenistic philosophers but with the ideas of the ancient world is frequently conveyed by the notion of 'sacred space', which the worshipper wishes to approach in order to gain access to the deity. Standing as he does within the religious tradition of Judaism, the author of Hebrews inherited notions of sacred space whereby it was identified with the land, Jerusalem, Zion and the sanctuary. He shares priestly concern, so Isaacs argues, to guard the sacred, to protect it from the profane, and to regulate the means whereby the worshipper can approach the holy.